2013
DOI: 10.1371/journal.pone.0072159
|View full text |Cite
|
Sign up to set email alerts
|

Default-Mode Network Changes in Huntington’s Disease: An Integrated MRI Study of Functional Connectivity and Morphometry

Abstract: Previous MRI studies of functional connectivity in pre-symptomatic mutation carriers of Huntington’s disease (HD) have shown dysfunction of the Default-Mode Network (DMN). No data however are currently available on the DMN alterations in the symptomatic stages of the disease, which are characterized by cortical atrophy involving several DMN nodes. We assessed DMN integrity and its possible correlations with motor and cognitive symptoms in 26 symptomatic HD patients as compared to 22 normal volunteers, by analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 83 publications
4
30
1
1
Order By: Relevance
“…This indicates that striatal and extra-striatal functional connectivity changes can occur simply because of regional brain volume loss and thus may not reflect activity changes independent from atrophy. This notion is in line with a recent study using BPM in early HD (Quarantelli et al 2013), which demonstrated that connectivity changes in the caudate nucleus and other cortical regions can be explained by regional atrophy. On the other hand, in patients BPM analyses also revealed areas of aberrant activity that were not apparent without atrophy correction.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that striatal and extra-striatal functional connectivity changes can occur simply because of regional brain volume loss and thus may not reflect activity changes independent from atrophy. This notion is in line with a recent study using BPM in early HD (Quarantelli et al 2013), which demonstrated that connectivity changes in the caudate nucleus and other cortical regions can be explained by regional atrophy. On the other hand, in patients BPM analyses also revealed areas of aberrant activity that were not apparent without atrophy correction.…”
Section: Discussionsupporting
confidence: 91%
“…Recent functional neuroimaging data obtained from patients with manifest HD indicate that some activity changes, e.g. in the caudate nucleus or in cortical regions, can be explained by regional atrophy (Quarantelli et al ., ). In line with previous studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Given the strong motor component in this disease, sensorimotor and basal ganglia-thalamocortical networks might be preferentially affected, although studies assessing these networks have provided mixed findings, some reporting reduced connectivity 91,92 and others reporting increased connectivity or mixed patterns. 93,94 These observations are not easy to interpret in view of the clear-cut and selective localization of HD pathology in the caudate nucleus, and the established role of this nucleus in large and well-defined corticostriatal loops (oculomotor, dorsolateral and ventral-orbital circuits). 95 Structural connectivity studies in HD have been more consistent.…”
Section: Huntington Diseasementioning
confidence: 99%